Analisis Struktur Bangunan Bawah pada Jembatan Way Lawa Tawiri Kota Ambon: Analysis of the Lower Structure of the Way Lawa Tawiri Bridge in Ambon City - Rumahlaiselan, Novalia Venesia; Siahaya, Vera Th. C.; Lewakabessy, Godfried (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
The bridges on Ambon Island in general are steel frame bridges, one of which includes the Way Lawa Tawiri Bridge in Ambon City, which has caused a narrowing of traffic flow so that it is necessary to rebuild the bridge. The purpose of this study is to analyze the loads acting on the abutments, the bearing capacity of the foundation soil, and its reinforcement (stumbling plate, stampede plate, console).The research method for this data was obtained: Field studies were carried out directly at the research location to obtain accurate data from the planning and implementation parties in the field, . Literature study in which the author used relevant data from books, journals and other scientific sources supports the theory and formulas used in calculations.Research results 1. Analysis of the calculated loading obtained by working loads: Dead load = 106.29 tons, Live load = 18.66 tons, Asphalt load = 113 tons, Friction load = 13.25 tons, Earthquake load = 3 .71 tons Active earth pressure (Pa), Pa1 = 58.21 tons Pa2 = 127.008 tons, Qult = 235.55 t/m2, Qall = 78.51 t/m2, Stumbling plate : Upper main reinforcement – ​​ϕ 13- 150 mm, Top reinforcement – ​​ϕ 13-300 mm, Bottom main reinforcement – ​​ϕ 25-150 mm Bottom reinforcement - ϕ16-160 mm. Step plate : Main reinforcement = ϕ 16-250 mm, Sectional reinforcement = ϕ 14-200 mm, Console : Main reinforcement = ϕ 25-165 mm, Sectional reinforcement = ϕ 12-165 m.